2020
DOI: 10.21776/ub.jrm.2020.011.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Parameter Pemotongan CNC Milling dalam Pembuatan Pocket terhadap Getaran dan Kekasaran Permukaan pada Crankcase Mesin Pemotong Rumput

Abstract: The purpose of the research is to find and prove the influence of machining parameters on vibration and roughness in the pocket milling process. The experimental method is used to improve the quality of products produced by CNC milling, the parameters used in the study are spindle rotation speed with variations of 300 rpm, 1200 rpm, and 3200 rpm, the depth of feed used is 2 mm and 0.5 mm. Then the test is carried out with a vibration test and surface roughness test. The data analysis technique used is descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
0
0
3
Order By: Relevance
“…From the surface roughness test that has been carried out and the graph above, it can be concluded that the higher the spindle speed used, the lower the surface roughness level, and the slower the spindle speed used, the higher the surface roughness level. These results are in accordance with research conducted by Kaisan [11]: the higher the spindle speed, the lower the roughness produced because the higher the spindle rotation, the greater the machine's effort to cut the workpiece so that the surface roughness will be low. As for the use of the zig-zag type of cutting direction, the roughness value is lower than that of the oneway type.…”
Section: Surface Roughness Testsupporting
confidence: 91%
“…From the surface roughness test that has been carried out and the graph above, it can be concluded that the higher the spindle speed used, the lower the surface roughness level, and the slower the spindle speed used, the higher the surface roughness level. These results are in accordance with research conducted by Kaisan [11]: the higher the spindle speed, the lower the roughness produced because the higher the spindle rotation, the greater the machine's effort to cut the workpiece so that the surface roughness will be low. As for the use of the zig-zag type of cutting direction, the roughness value is lower than that of the oneway type.…”
Section: Surface Roughness Testsupporting
confidence: 91%
“…CNC merupakan mesin canggih yang digerakkan menggunakan program [3] . Faktorfaktor yang mempengaruhi keunggulan CNC dibandingkan mesin konvensional diantaranya adalah tidak banyak setting, tool berpindah secara otomatis sesuai program yang diminta, pergerakan mesin dapat dimonitor pada layar monitor, tingkat error kecil, dan efesiensi waktu [4] .…”
Section: Pendahuluanunclassified
“…Begitu juga pada spindle yang berfungsi sebagai pemutar benda kerja pada mesin perkakas CNC. CNC merupakan mesin canggih yang digerakkan menggunakan program [5]. Spindle mesin bubut CNC merupakan bagian yang sangat penting dalam menghasilkan produk yang berkualitas dan bermutu.…”
Section: Pendahuluanunclassified